Retrosplenial cortex in spatial memory: focus on immediate early genes mapping - Balcerek, Edyta; Włodkowska, Urszula; Czajkowski, Rafał (Molecular brain, 2021)
The ability to form, retrieve and update autobiographical memories is one of the most fascinating features of human behavior. Spatial memory, the ability to remember the layout of the external environment and to navigate within its boundaries, is closely related to the autobiographical memory domain. It is served by an overlapping brain circuit, centered around the hippocampus (HPC) where the cognitive map index is stored. Apart from the hippocampus, several cortical structures participate in this process. Their relative contribution is a subject of intense research in both humans and animal models. One of the most widely studied regions is the retrosplenial cortex (RSC), an area in the parietal lobe densely interconnected with the hippocampal formation. Several methodological approaches have been established over decades in order to investigate the cortical aspects of memory. One of the most successful techniques is based on the analysis of brain expression patterns of the immediate early genes (IEGs). The common feature of this diverse group of genes is fast upregulation of their mRNA translation upon physiologically relevant stimulus. In the central nervous system they are rapidly triggered by neuronal activity and plasticity during learning. There is a widely accepted consensus that their expression level corresponds to the engagement of individual neurons in the formation of memory trace. Imaging of the IEGs might therefore provide a picture of an emerging memory engram. In this review we present the overview of IEG mapping studies of retrosplenial cortex in rodent models. We begin with classical techniques, immunohistochemical detection of protein and fluorescent in situ hybridization of mRNA. We then proceed to advanced methods where fluorescent genetically encoded IEG reporters are chronically followed in vivo during memory formation. We end with a combination of genetic IEG labelling and optogenetic approach, where the activity of the entire engram is manipulated. We finally present a hypothesis that attempts to unify our current state of knowledge about the function of RSC.